In order to realizing settled development and have the continuation, contribution of each sector of development in PDRB have to be non-stopped to be improved, among other things through optimality of development of nature resources owned. This research aim to know perfonnance, role and affect fishery and oceanic sector in Regency Kendal, so that can be fonnulated by altemative of development strategy. This research use case study method, data analyzed to use analysis of location quotient, multip - M Prihatna Sobari; Nova Arifatul Farida (Buletin Ekonomi Perikanan, 2007)
In order to realizing settled development and have the continuation, contribution of each sector of development in PDRB have to be non-stopped to be improved, among other things through optimality of development of nature resources owned. This research aim to know perfonnance, role and affect fishery and oceanic sector in Regency Kendal, so that can be fonnulated by altemative of development strategy. This research use case study method, data analyzed to use analysis of location quotient, multiplier effect and SWOT. Dl,lring period of year 1999-2003, fishery product, fishery labor, appliance catch and annada of arrest of fishery and oceanic sector in Regency of Kendal progressively mount. Pursuant to indicator of regional eamings and labor, fishery and oceanic sedor represent sedor of bases in economics in region of Regency Kendal. Thereby, fIShery and oceanic sector of Regency of Kendal able to create opportunity work to fulfill requirement of market in region and also request of market of outside region or export. This condition will enlarge current of eamings into region of Regency Kendal, so that push improvement of request socialize to do well by product of fIShery and also product of other sedor, and indirectly will improve regional eamings. Election of strategy altemative which is given high priority for development of fIShery and oceanic sedor of Regency Kendal, is do development of interpoSing of fishery and oceanic sedor with inwrought approach and have the continuation to exploited is potency of big oceanic resources, labor of-and accessibility fishery easy to got and also existence of support from local govemment of through program of construction and utilizations socialize coastal area, utilize to fulfill local requirement and also export